ANALISIS POLA KONSUMSI RUMAH TANGGA PETANI JAGUNG DI KABUPATEN GROBOGAN - Fajar Prasetyoningrum; Endang Siti Rahayu; Sri Marwanti (Agric, 2016)
ABSTRACTThis study aims to analyze the broad influence corn field to the household income of corn farmers in Grobogan district, analyze the effect of educational level the head of family to the household income of corn farmers in Grobogan district, analyze the effect of the number of family members to the household income of corn farmers in Grobogan district, analyze the effect the food and non food expenditure to the household income of corn farmers in Grobogan district. Locations were taken intentionally, in Grobogan district, because Grobogan district has the widest corn harvested area in the province of Central Java. Total population that taken in this study is 150 household of corn farmers who scattered in several regions in Grobogan. The sample is a fraction of the number and characteristics which is owned by the population. Samples were corn farmers, the number of samples taken is 60 corn farmers in Grobogan. The results showed that land area of corn gave positive effect on household income of corn farmers in Grobogan, the educational level of husband’s household insignificant, the number of household members has a positive influence on the level of household income, food expenditure had a negative but not significant to household income and non-food expenditures have a significant negative effect on the level of household income. The result of the calculation of the proportion of food consumption and the proportion of non-food consumption showed that the average total expenditure for average food expenditure per farmer per month amounted Rp. 1.023.611,00 while the non-food expenditure amounted Rp. 2.619.552,00.